PENGARUH PERTUMBUHAN EKONOMI DAN PENGELUARAN PEMERINTAH TERHADAP KEMISKINAN DI KALIMANTAN BARAT TAHUN 2009-2013 - B61112034, DEFFRINICA (Jurnal Ekonomi Daerah (JEDA), 2015)
ABSTRACK Relationships economic growth of government expenditure indicates that both government expenditure and development expenditure routine expenditure, which is in need by developing an appropriate area and the potential that exists in the region so as to reduce the number of poor people. The need for analysis of the development of economic growth and government spending in the province of West Kalimantan so that we can determine the extent of economic growth and government spending to reduce poverty in the region. The relationship of economic growth and government spending, a positive and significant impact on poverty in West Kalimantan. The influence of economic growth on poverty is positive and significant, while public spending is also positive and significant. Â